Highly Selective and Catalytic Oxygenations of C−H and C=C Bonds by a Mononuclear Nonheme High‐Spin Iron(III)‐Alkylperoxo Species. Issue 36 (1st August 2019) - Ghosh, Ivy; Banerjee, Sridhar; Paul, Satadal; Corona, Teresa; Paine, Tapan Kanti
Abstract: The reactivity of a mononuclear high‐spin iron(III)‐alkylperoxo intermediate [Fe III ( t ‐BuL Urea )(OOCm)(OH2 )] 2+ (2 ), generated from [Fe II ( t ‐BuL Urea )(H2 O)(OTf)](OTf) (1 ) [ t ‐BuL Urea =1, 1′‐(((pyridin‐2‐ylmethyl)azanediyl)bis(ethane‐2, 1‐diyl))bis(3‐(tert‐butyl)urea), OTf=trifluoromethanesulfonate] with cumyl hydroperoxide (CmOOH), toward the C−H and C=C bonds of hydrocarbons is reported. 2 oxygenates the strong C−H bonds of aliphatic substrates with high chemo‐ and stereoselectivity in the presence of 2, 6‐lutidine. While 2 itself is a sluggish oxidant, 2, 6‐lutidine assists the heterolytic O−O bond cleavage of the metal‐bound alkylperoxo, giving rise to a reactive metal‐based oxidant. The roles of the urea groups on the supporting ligand, and of the base, in directing the selective and catalytic oxygenation of hydrocarbon substrates by 2 are discussed. Abstract : Role playing : A transient ( t 1/2 =3 min at 283 K) high‐spin iron(III)‐alkylperoxo intermediate, supported by a ligand bearing urea groups, exhibits selective and catalytic oxygen‐atom transfer and hydrogen atom transfer reactions in the presence of a general‐base promoter. The urea groups on the ligand backbone play a pivotal role in driving the selectivity and catalytic activity.